Congenital diverticulum of the right atrium situated on the floor of the coronary sinus. Issue 6 (June 1988) - Petit, A; Eicher, J C; Louis, P
Abstract : A diverticulum of the right atrium was found on the floor of the coronary sinus in a neonate. The diverticulum was distinguished from a pericardial cyst by contrast echocardiography, and its relations with coronary sinus and coronary venous return were identified by coronary angiography. Because the diverticulum compressed the left ventricular inferior wall and prevented its growth, it was excised. Thebesian veins were discovered at operation and prevented complete correction of the defect.